Evaluation of behavior factor of tunnel‐form concrete building structures using Applied Technology Council 63 methodology. Issue 8 (9th June 2011) - Tavafoghi, Alireza; Eshghi, Sassan
SUMMARY Tunnel‐form construction system is used for buildings made up of slabs and walls. This system has represented fast construction technique, low cost and time saving in the construction period. However, there are no special requirements for seismic design of this type of buildings, and some provisions of the concrete bearing wall system are used. None of the seismic codes addresses the R factor for tunnel‐form buildings directly, and some doubts remained about prediction of the fundamental period. Meanwhile the force‐based methods, which depended on R factor and fundamental period, are still used for seismic design of this type of buildings. There is a need for evaluating the R factor for tunnel‐form buildings. The methodology was developed by the Applied Technology Council (ATC) entitled ATC‐63 Project for quantifying building system performance and response parameters for use in seismic design. Here, this methodology is used to estimate more reliable R factor for tunnel‐form buildings. An experimental program was carried out to decrease the uncertainty of finite element modeling and using it as a part of the methodology. A database was created, and some analyses were performed. The results of analysis were summarized to propose more accurate R factor for tunnel‐form buildings. Copyright © 2011 John Wiley & Sons, Ltd.